Sexually transmitted hepatitis C virus infections: current trends, and recent advances in understanding the spread in men who have sex with men. (30th August 2019) - Nijmeijer, Bernadien M; Koopsen, Jelle; Schinkel, Janke; Prins, Maria; Geijtenbeek, Teunis BH
Abstract: Introduction: Hepatitis C virus (HCV) is a major public health threat. Although the recent availability of highly effective directly acting antivirals created optimism towards HCV elimination, there is ongoing transmission of HCV in men who have sex with men (MSM). We here report current epidemiological trends and synthesise evidence on behavioural, network, cellular and molecular host factors associated with sexual transmission of HCV, in particular the role of HIV‐1 co‐infection. We discuss prevention opportunities focusing on the potential of HCV treatment. Methods: We searched MEDLINE, fact sheets from health professional bodies and conference abstracts using appropriate keywords to identify and select relevant reports. Results and discussion: Recent studies strongly suggest that HCV is transmitted via sexual contact in HIV‐positive MSM and more recently in HIV‐negative MSM eligible for or on pre‐exposure prophylaxis. The reinfection risk following clearance is about 10 times the risk of primary infection. International connectedness of MSM transmission networks might contribute to ongoing reinfection. Some of these networks might overlap with networks of people who inject drugs. Although, the precise mechanisms facilitating sexual transmission remain unclear, damage to the mucosal barrier in the rectum could increase susceptibility. Mucosal dendritic cell subsets could increase HCV susceptibility by retaining HCV and transmitting the virus to other cells, allowing egress into blood and liver. Early identification of new HCV infections is important to prevent onward transmission, but early diagnosis of acute HCV infection and prompt treatment is hampered by the slow rate of HCV antibody seroconversion, which in rare cases may take more than a year. Novel tests such as testing for HCV core antigen might facilitate early diagnosis. Conclusions: High‐risk sexual behaviour, network characteristics, co‐infection with sexually transmitted infections like HIV‐1 and other concomitant bacterial and viral sexually transmitted infections are important factors that lead to HCV spread. Targeted and combined prevention efforts including effective behavioural interventions and scale‐up of HCV testing and treatment are required to halt HCV transmission in MSM.